2015
DOI: 10.1186/s12889-015-1651-3
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and drinking frequency of alcoholic beverage among women in Ghana: a cross-sectional study

Abstract: BackgroundThe consumption and drinking frequency of alcoholic beverage are identified with various individual factors. The aim of this study was to identify background characteristics of women associated with the consumption and drinking frequency of alcoholic beverage.MethodsData was extracted from the 2008 Ghana Demographic and Health Survey. The data consisted of women’s (aged 15–49 years) background characteristics and their reported history of consumption and drinking frequency of alcoholic beverage. A we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Civil servants were 4.4 times more likely to engage in dependent drinking, relative to moderate drinking, compared to those who were not employed. This view is consistent with the previous findings that affluent people are more likely to drink more alcohol than less affluent ones and more likely to engage in hazardous drinking [ 13 , 14 ]. It is also consistent with the findings by the Ghana Statistical Service that found that the prevalence of alcohol consumption was higher among women who were employed than those who were unemployed [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Civil servants were 4.4 times more likely to engage in dependent drinking, relative to moderate drinking, compared to those who were not employed. This view is consistent with the previous findings that affluent people are more likely to drink more alcohol than less affluent ones and more likely to engage in hazardous drinking [ 13 , 14 ]. It is also consistent with the findings by the Ghana Statistical Service that found that the prevalence of alcohol consumption was higher among women who were employed than those who were unemployed [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…32 However, the prevalence of lifetime alcohol use among the older, adult female population was 10%, lower than the 17.5% reported among a relatively younger Ghanaian population of 15-49 year olds by Tampah-Naah and Amoah. 33 Also, alcohol use was higher among the non-religious than the religious. Among the religious, fewer Muslims than Christians and the primal indigenous used alcohol.…”
Section: Discussionmentioning
confidence: 98%
“… 32 However, the prevalence of lifetime alcohol use among the older, adult female population was 10%, lower than the 17.5% reported among a relatively younger Ghanaian population of 15–49 year olds by Tampah-Naah and Amoah. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In some societies, alcohol use is seen as a symbol of virility, courage, and success associated with masculinity (Ferreira-Borges et al, 2017;Peralta et al, 2010;Rich et al, 2015). Studies in Ghana suggest alcohol use, including binge drinking, is relatively high in certain parts of the country and among some sociocultural groups (Tampah-Naah & Amoah, 2015;Yawson et al, 2015). Yawson et al (2015) observed that binge drinking was more prevalent in the three northern regions of Ghana.…”
Section: Introductionmentioning
confidence: 99%